Assessment of the Glenoid Morphology Based on Demographic Data in the Turkish Population - BİLSEL, İSMAIL KEREM; Sari, Abdulkadir; Dincel, Yasar Mahsut; Gunaydin, Burak; Cetin, Mehmet umit; Ozcaglayan, Omer; Bilsel, Kerem (My University, 2020)
Purpose. In this study, our aim was to evaluate the glenoid version, height, and width measurements based on gender, side, age, height, and hand dominance in the Turkish population using computed tomography (CT) images. Methods. In our study, CT images of 140 patients (62 females and 78 males; mean age: 39.6 years) who had no shoulder complaints were evaluated retrospectively. Glenoid version (GV), AP diameter (width), and SI diameter (height) on both shoulders were measured on the CT images. Correlations between patient gender, side, age, height, and hand dominance and the GV and size were evaluated. Results. The right shoulder had a mean GV of -0.93 +/- 7.80 degrees and the left shoulder had a GV of -0.88 +/- 6.63 degrees (p>0.05). The mean AP diameter of the glenoid was 26.57 +/- 3.02 mm in the right shoulder and 26.33 +/- 3.01 mm in the left shoulder (p>0.05). The mean SI diameter of the glenoid was 31.8 +/- 3.6 mm in the right and 31.7 +/- 3.3 mm in the left shoulder (p>0.05). When men and women were evaluated in two separate groups, the GV, AP, and SI values did not exhibit a statistically significant difference between the two shoulders in both genders (p>0.05). There was a positive correlation between the ages and heights of the patients and the glenoid size (p<0.05). The mean AP diameter was approximately 28 mm and the SI diameter was 34 mm in males, whereas the mean AP diameter was 24 mm and the SI diameter was 30 mm in females (p<0.05). The GV values of the dominant shoulders were significantly more retroverted (p<0.05). There was a positive correlation between the ages and heights of the patients and the glenoid size (p<0.05). Conclusion. Hand dominance had an effect on the glenoid version, while patient gender, age, and height had an effect on the glenoid size. The glenoid width in the Turkish population was similar to that of the European and American populations, and the glenoid height was similar to that of the Asian population. Our GV values were similar to those of the Asian population and more anteverted compared to the Western population. We believe that our findings will be useful in preoperative planning and in the production of implants for our population.
Keywords: Turkish Population